Satellite DNa polymorphisms and AFLP correlate with Bos indicus-taurus hybridization - Nijman, I.J.; Bradley, D.G.; Hanotte, Olivier H.; Otsen, M.; Lenstra, J.A. (Wiley, 1999)
We describe satellite DNA variation that detects hybridization of Bos indicus (Zebu or indicine cattle) and Bos taurus (taurine cattle) in African cattle populations. On southern blots hybridized to a satellite III probe, relative intensities of Hinf1 fragments correlated with the taurine-zebu composition in hybrid animals as deduced from AFLP genotyping of the same animals and previous data on microsatellite allele frequencies. Similar results were obtained by PCR-RFLP analysis of a zebu-specific mutation in the repeat unit of satellite 1.711b. analysis of individulas from 20 African cattle breeds indicate that the centromeric satellites of the sanga breeds are of the taurine type and that several East-African zebu breeds are hybrids between taurine and zebu. These satellite RFLP or SFLP, markers provide a fast method to screen the genetic makeup of African cattle.